INTERNALISASI NILAI AMANAH MELALUI PENDIDIKAN ANTI KORUPSI DALAM PENGUATAN KARAKTER INTEGRITAS PESERTA DIDIK - Dewa Mahendra Adi Saputra; Samsuri; Ansori (LPPM STAI Muhammadiyah Probolinggo, 2026)
Corruption is a multidimensional problem that causes material losses, moral degradation, and weakened social integrity. This study aims to analyze the internalization of the value of amanah (trustworthiness) through anti-corruption education in strengthening students’ integrity character in schools. This research employed a qualitative approach using library research. Data were collected from books, journal articles, educational regulations, and previous studies related to anti-corruption education, character education, and amanah values in Islamic education. Data analysis used descriptive-analytical content analysis. The findings reveal that the internalization of amanah values can be implemented through integrated learning, school culture, teachers’ role modeling, and habituation of honest and responsible behavior. Anti-corruption education based on amanah values contributes significantly to strengthening students’ integrity character as a preventive effort against corruptive behavior from an early age. Therefore, anti-corruption education functions not only as knowledge transfer but also as a process of moral and ethical character formation.